Methodology for predicting maximum velocity and shear stress in a sinuous channel with bendway weirs using 1-D HEC-RAS modeling results - Sclafani, Paul, author; Thornton, Christopher I., advisor; Watson, Chester C., committee member; Wohl, Ellen E., 1962-, committee member (Colorado State University. Libraries, 2010)
The Middle Rio Grande is a 29-mi reach of the Rio Grande River in central New Mexico that extends from downstream of Cochiti Dam to Bernalillo, New Mexico. A series of anthropogenic factors including the construction of flood control levees and Cochiti Dam have altered the historically-braided morphology of the Middle Rio Grande to a more sinuous, degrading reach, with less overall channel migration within a natural floodplain area. Concentration of flow within an incised channel has caused areas of bank erosion and threatened riverside infrastructure, farmland productivity, irrigation systems, levee function, aquatic habitat, and riparian vegetation. Colorado State University (CSU) constructed an undistorted 1:12 Froude scale, fixed bed, physical model consisting of two channel bend geometries that are characteristic of the Middle Rio Grande reach below Cochiti Dam. Small rock structures extending from the outer bank of the bend into the main channel, referred to as bendway weirs, were constructed within each bend to research methods of stabilizing the outer bank with minimal disruption of sensitive habitat and riparian vegetation. Bendway weirs deflect current from the bank in which they are installed to the center of the channel, thus, moving erosive forces away from a degrading bank, establishing a stable channel, and providing or maintaining aquatic habitat between weir structures. Placement of bendway weirs along a river bank effectively creates two zones of flow: 1) the main or constricted flow where the velocity, shear stresses, and potential for channel degradation are increased, and 2) the area between weirs where velocities and shear stresses are greatly reduced and sediment deposition is encouraged. Design criterion to predict increases in velocity and shear stress caused by placement of bendway weirs in a channel bend has not yet been established. Two-dimensional and three-dimensional computer models have been utilized to describe complex flow phenomena associated with bendway weirs in channel bends; however, such computer models may not be practical for typical design projects (Jia et al., 2005; Molls, et al., 1995; Abad et al., 2008; Seed, 1997). Because of historic precedence, continual development, and prevalence in the engineering community, many engineers use one-dimensional (1-D) computer modeling tools, such as Hydrologic Engineering Center's River Analysis System (HEC-RAS), as a first choice in modeling channel flow. 1-D computer models were developed for the trapezoidal channel geometry present in the physical model and for fifteen weir configurations constructed during testing at CSU. Computed results from the 1-D models were compared to data collected from the Middle Rio Grande physical model. Regression relationships were developed to predict velocities and shear stresses in the trapezoidal channel constructed for physical testing at CSU, at the tips of the constructed bendway weirs, and along the inner bank opposite the constructed bendway weirs. From predictive regression relationships for the velocity and shear stress in channel bends, with and without bendway weirs, a four-step design process was developed to provide practicing engineers with guidance that can be used to design bendway weir fields.
Department Head: Luis A. Garcia.